2019
DOI: 10.1101/760702
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Developing a dengue forecast model using Long Short Term Memory neural networks method

Abstract: 22Background 23 Dengue Fever (DF) is a tropical mosquito-borne disease that threatens public health 24 and causes enormous economic burdens worldwide. In China, DF expanded from 25 coastal region to inner land, and the incidence sharply increased in the last few years. 26In this study, we conduct the analysis of dengue using the Long Short Term Memory 27 (LSTM) recurrent neural networks. This is an artificial intelligence technology, to 28 develop a precise dengue forecast model. 29 Methodology/Principal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…They observed that this accuracy level resulted from the increase in the number of iterations contributing to the decrease in the root mean squared error (RMSE). Xu et al [16] developed a timely and accurate forecasting model for dengue fever cases in China using LSTM. The researchers compared the performance of LSTM models with other previously published models when predicting dengue fever cases one month into the future.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They observed that this accuracy level resulted from the increase in the number of iterations contributing to the decrease in the root mean squared error (RMSE). Xu et al [16] developed a timely and accurate forecasting model for dengue fever cases in China using LSTM. The researchers compared the performance of LSTM models with other previously published models when predicting dengue fever cases one month into the future.…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to the empirical research, the proposed strategy is a good one, according to the results of the experimental study. Xu et al (2020) developed an efficient and effective dengue forecasting model using LSTM recurrent neural networks (Xu et al, 2019). Only monthly dengue cases and climate conditions were considered in the study.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There are some symptoms, including a high fever and a skin rash. Bleeding, low blood platelet levels and blood plasma leakage or shock syndrome can occur in a tiny percentage of cases (Xu et al, 2019;Zhang, Su, & Chen, 2021). When a mosquito assaults someone with dengue fever, they've been nibbled by a mosquito carrying the dengue worm.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, such methods fail to detect long anomalies as they do not capture the long-range temporal dependencies. With the recent success of transformers in computer vision which are empowered by multi-head selfattention [9], many popular methods in fully-supervised action detection [17,40] and classification have leveraged temporal transformers for effective global temporal relation encoding. However, weakly-supervised anomaly detection tasks can not get direct benefits from the current temporal transformers, due to (i) conventional positional encoding: unlike fully-supervised settings, where the temporal positions have a one-to-one correspondence with the anomaly instances for superior global temporal relation encoding, the weakly-supervised methods do not have such correspondences due to the unavailability of the instance labels; (ii) naive tokenization scheme: existing methods follow a fixed-scale tokenization scheme regardless of the action duration, as a result these methods can not accumulate local contextual information for long anomalies.…”
Section: Introductionmentioning
confidence: 99%